Raspberry Pi user guide - Upton, Eben; Halfacree, Gareth (John Wiley & Sons, 2012)
The essential guide to getting started with the Raspberry Pi ® The Raspberry Pi has been a success beyond the dream of its creators. Their goal, to encourage a new generation of computer programmers who understand how computers work, is well under way. Raspberry Pi User Guide 2e is the newest edition of the runaway bestseller written by the Pi's co-creator, Eben Upton, and tech writer Gareth Halfacree. It contains everything you need to know to get the Pi up and running, including how to: Connect a keyboard, mouse, monitor and other peripherals Install software and configure your Raspberry Pi Master basic Linux system administration Set up your Raspberry Pi as a productivity machine, multimedia centre, or web server Write programmes in Scratch and Python Use the GPIO port and add-on boards to connect your Raspberry Pi for use in electronics projects Updated to cover the release of the Camera Board, the introduction of the Pi Store, NOOBS and much more, Raspberry Pi User Guide 2nd edition is the perfect companion for getting the most out of the computing phenomenon, the Raspberry Pi. Eben Upton is the co-creator of the Raspberry Pi board and the founder of the Raspberry Pi Foundation. Gareth Halfacree is a freelance technology journalist, open source advocate and erstwhile sysadmin.